Obstructive sleep apnea is not an independent determinant of testosterone in men. Issue 1 (July 2020) - Clarke, Brigette Marie; Vincent, Andrew D; Martin, Sean; Adams, Robert; Appleton, Sarah; Vakulin, Andrew; Jesudason, David; Wittert, Gary Allen
Abstract : Objective: Obstructive sleep apnea (OSA) is generally considered to lower serum testosterone concentration in men, although data supporting this as a direct effect are limited. The aim of this study was to determine the relationship between the presence and severity of OSA and testosterone in a community-based cohort of men aged over 40 years. Design and methods: Anthropometry, polysomnography and biomedical information were collected from enrolled, consenting men from the prospective, longitudinal MAILES study cohort. Fasting morning blood samples ( n = 1869) were drawn between 2010 and 2012 for measurement of testosterone using liquid chromatography mass spectrometry. Home polysomnography was completed in 861 men between 2010 and 2012. The final analysis sample consisted of 623 men aged 41–86 years. The effect of OSA on testosterone were analyzed using linear regression models controlling for potential confounders (age, BMI and sex hormone binding globulin (SHBG)). Results: The mean (s.d. ) cohort characteristics were: age 59.0 (10.2) years, testosterone 16.8 (5.3) nmol/L, SHBG 32.9 (13.1) nmol/L, BMI 28.6 (4.2) kg/m 2 and apnoea hypopnoea index (AHI) 14.9 (13.7). OSA was present in 51.5%. There was an inverse relationship between AHI and testosterone ( P = 0.01), which was lost after covariate adjustment. Conclusions: These data suggest that obesity, rather than OSA per se, determine testosterone concentration. This accords with the graded effect of weight loss, but limited effect of continuous positive airway pressure to increase testosterone, and highlights the importance of managing obesity in men with low testosterone concentration, particularly in the context of OSA.